Nano smoke suppressant as well as preparation method and application thereof

Through the combination of graphene and daidine-based benzoxazine resin with copper-loaded laser induced, the problems of insufficient flame retardancy and high smoke toxicity of benzoxazine resin are solved, and high-performance flame retardant and smoke suppression effect are achieved. Suitable for high-demand application areas.

CN119192685APending Publication Date: 2024-12-27NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411598949.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing benzoxazine resin has insufficient intrinsic flame retardancy, and a large amount of thick smoke and toxic gases are generated during combustion, which limits its application in aerospace and other fields.

Method used

The copper-loaded laser-induced graphene is used as a nano-smoke inhibitor, combined with daidine-based benzoxazine resin, and the flame-retardant and smoke-resistant benzoxazine nanocomposite is prepared by laser ablation treatment and step-up temperature curing. The free radical capture and catalyzed carbonization of metal oxides and nanomaterials significantly improves flame retardant and smoke suppression performance.

Benefits of technology

It significantly improves the flame retardant and smoke suppression properties of composite materials, reduces the smoke release during combustion, and is suitable for electronic packaging, aerospace and rail transit fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192685A_ABST
    Figure CN119192685A_ABST
Patent Text Reader

Abstract

The invention discloses a nano smoke suppressant as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing a copper source, phenol-4, 4 '-diaminodiphenylmethane benzoxazine and a solvent, and then removing the solvent, curing and performing laser ablation treatment to prepare the copper-loaded laser-induced graphene nano smoke suppressant. According to the preparation method disclosed by the invention, the nano smoke suppressant of the copper-loaded laser-induced graphene is combined with the intrinsic flame-retardant high-char-forming daidzein-based benzoxazine resin, so that the flame-retardant and smoke-suppressing properties of the prepared composite material are remarkably improved; meanwhile, the composite material can be used as a high-performance resin matrix or structural material to be applied to the fields of electronic packaging, aerospace, rail transit and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of benzoxazine functional modification, and relates to a nano smoke suppressant and a preparation method and application thereof, and in particular to a nano smoke suppressant, a flame retardant and smoke suppressant benzoxazine nanocomposite material and a preparation method and application thereof. Background Art

[0002] As a new type of thermosetting resin, benzoxazine resin has the advantages of excellent heat resistance, good flame retardancy, high mechanical properties, near-zero release / near-zero shrinkage during curing, etc. It has a wide range of applications in aerospace, charging and discharging equipment, military industry, coatings, etc. However, the commercially available benzoxazine resins generally have the problem of insufficient intrinsic flame retardancy, and the UL-94 grade is usually not higher than V-1, especially when burned, it is easy to produce a large amount of thick smoke and toxic gases. According to the number of casualties in fires in recent years, more than 80% are caused by suffocation caused by toxic smoke. Insufficient flame retardancy and high smoke toxicity not only easily cause fire accidents, but also seriously limit the application of such materials in aerospace, rail transportation and other fields. Therefore, how to improve the intrinsic flame retardancy of benzoxazine resins and reduce their smoke release and smoke toxicity during combustion is of great significance.

[0003] To solve the above problems, the commonly used method is to add or introduce halogen-containing or phosphorus-containing flame retardant components. Although this method has greatly improved the flame retardant properties of the material, the product will produce gases harmful to the environment during combustion, and the problem of smoke toxicity has not been solved. For example, the patent with publication number CN105131283A discloses a fluorine-containing nitrogen benzoxazine polymer flame retardant and a preparation method thereof. A cyclotriphosphazene-type benzoxazine resin is obtained by reacting a formaldehyde aqueous solution, a primary amine compound and a triphosphazene-containing phenol, which has excellent heat resistance and flame retardant properties. However, the monomer synthesis of this method is relatively complicated and contains more flame retardant elements.

[0004] Nano flame retardants are a new type of high-efficiency flame retardant, such as nano carbon tubes, graphene, nano metal hydroxides, etc., which have the advantages of large specific surface area, high surface activity, good dispersibility, and good influence on materials. In addition, nano flame retardants can capture free radicals generated during polymer combustion, suppress smoke, and catalyze carbonization, which can reduce smoke release during combustion to a certain extent. Therefore, the development of new high-efficiency nano flame retardant and smoke suppressant is expected to solve the problems of insufficient intrinsic flame retardancy of benzoxazine and high toxicity of combustion smoke. Summary of the invention

[0005] The main purpose of the present invention is to provide a nano smoke suppressant and a preparation method and application thereof, so as to overcome the problems of insufficient flame retardancy of commercially available benzoxazine in the prior art, large smoke release and high smoke toxicity when the flame retardant modified benzoxazine is burned.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: An embodiment of the present invention provides a method for preparing a nano smoke suppressant, which comprises: mixing a copper source, phenol-4,4'-diaminodiphenylmethane type benzoxazine and a solvent, and then removing the solvent, curing, and laser ablation to obtain a nano smoke suppressant of laser induced graphene loaded with copper.

[0007] The embodiment of the present invention also provides a nano smoke suppressant prepared by the aforementioned preparation method.

[0008] The embodiment of the present invention also provides a method for preparing a flame retardant and smoke suppressant benzoxazine nanocomposite material, which comprises: mixing the aforementioned nano smoke suppressant with a soybean aglycone-based benzoxazine resin and performing a curing treatment to obtain a flame retardant and smoke suppressant benzoxazine nanocomposite material.

[0009] The embodiment of the present invention also provides a flame retardant and smoke suppressing benzoxazine nanocomposite material prepared by the aforementioned preparation method.

[0010] The embodiments of the present invention also provide the use of the flame retardant and smoke suppressing benzoxazine nanocomposite material as a high-performance resin matrix or structural material in the fields of electronic packaging, aerospace or rail transportation.

[0011] Compared with the prior art, the beneficial effect of the present invention is that: based on the mechanism of metal oxides and nanomaterials that can capture free radicals generated during polymer combustion, suppress smoke and catalyze carbonization, the present invention prepares a copper-loaded laser-induced graphene nano smoke suppressant, combined with an intrinsically flame-retardant and high-carbonizing soybean aglycone-based benzoxazine resin, thereby significantly improving the flame retardancy and smoke suppression properties of the prepared composite material. At the same time, the composite material can be used as a high-performance resin matrix or structural material in electronic packaging, aerospace, rail transportation and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0013] Figure 1 It is the X-ray diffraction spectrum of the phenol-4,4'-diaminodiphenylmethane type benzoxazine and the nano smoke suppressant in Example 1 of the present invention. DETAILED DESCRIPTION

[0014] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. It mainly provides a preparation method and application of a flame-retardant and smoke-suppressing benzoxazine nanocomposite material. The obtained nanocomposite material has excellent flame retardant properties and extremely low smoke release during combustion, and has good application potential in the fields of electronic packaging, aerospace, and rail transportation.

[0015] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a nano smoke suppressant involves: mixing a copper source, phenol-4,4'-diaminodiphenylmethane type benzoxazine and a solvent, and then removing the solvent, curing, and laser ablation to obtain a nano smoke suppressant loaded with copper laser-induced graphene.

[0017] In some preferred embodiments, the preparation method specifically comprises: The copper source, phenol-4,4'-diaminodiphenylmethane type benzoxazine and a solvent are mixed, stirred and ultrasonically treated to prepare a homogeneous mixed solution; The homogeneous mixed solution is subjected to vacuum removal of solvent and stepwise temperature curing treatment to obtain a solidified product; And, the solidified material is subjected to laser ablation treatment and stripping treatment to obtain a nano smoke suppressant of laser-induced graphene loaded with copper.

[0018] Furthermore, the copper source includes any one or more combinations of copper acetylacetonate compounds, bismuthocene compounds, carbonyl compounds, and organic phosphine compounds, but is not limited thereto.

[0019] Further, the solvent includes any one or more combinations of acetone, tetrahydrofuran, chloroform, dichloromethane, N,N-dimethylformamide, and dimethyl sulfoxide, but is not limited thereto.

[0020] Furthermore, the mass ratio of the copper source to phenol-4,4'-diaminodiphenylmethane type benzoxazine is 1-20:80-99.

[0021] Furthermore, the temperature used for vacuum removal of the solvent is 40-80°C.

[0022] Furthermore, the process parameters of the step-temperature curing treatment include: first curing at 160-180° C. for 1-10 hours, and then curing at 180-205° C. for 1-10 hours.

[0023] Furthermore, the laser used in the laser ablation process includes a carbon dioxide laser, but is not limited thereto.

[0024] Furthermore, the laser power used in the laser ablation process is 5-25W.

[0025] Furthermore, the scanning mode in the laser direct writing process used in the laser ablation treatment is a raster mode, the speed is 1-500 mm / s, the pixel density is 200-1200 PPI, and the defocus distance is 0-6 mm.

[0026] In some more specific embodiments, the method for preparing the copper-loaded laser-induced graphene nano smoke suppressant comprises the following steps: (1) dissolving copper acetylacetonate and phenol-4,4'-diaminodiphenylmethane benzoxazine (PH-ddm) in a certain proportion in an organic solvent, and obtaining a homogeneous mixed solution by stirring and ultrasonication; (2) transferring the mixed solution to a mold, removing the solvent under vacuum, and curing by stepwise heating to obtain a sheet-like solidified product; (3) The solidified material is subjected to laser ablation with specific parameters, and the surface ablation layer is peeled off and collected to obtain a nano smoke suppressant of laser-induced graphene loaded with copper.

[0027] Preferably, in step (1), the mass ratio of copper acetylacetonate to PH-ddm in the mixed solution is 1-20 parts:80-99 parts, and the organic solvent comprises any one or more of acetone, tetrahydrofuran, chloroform, dichloromethane, N,N-dimethylformamide, and dimethyl sulfoxide.

[0028] Preferably, the temperature range of the vacuum solvent extraction in step (2) is 40-80°C, and the step temperature curing procedure is 160-180°C / 1 hour-10 hours, 180-205°C / 1 hour-10 hours.

[0029] Preferably, the laser used in step (3) is a carbon dioxide laser.

[0030] Preferably, the laser power during the laser processing in step (3) is 5-25 W.

[0031] Preferably, in the laser direct writing process in step (3), the scanning mode is a raster mode, the speed is 1-500 mm / s, the pixel density is 200-1200 (PPI), the defocus distance is 0-6 mm, and the z-axis value is determined according to the actual thickness of the substrate.

[0032] Another aspect of the embodiments of the present invention further provides a nano smoke suppressant prepared by the aforementioned preparation method.

[0033] Another aspect of the embodiments of the present invention further provides a method for preparing a flame retardant and smoke suppressant benzoxazine nanocomposite material, which comprises: mixing the aforementioned nano smoke suppressant with a soybean aglycone-based benzoxazine resin and performing a curing treatment to obtain a flame retardant and smoke suppressant benzoxazine nanocomposite material.

[0034] In some preferred embodiments, the daidzein-based benzoxazine resin has a structure as shown in formula (I): ; Formula (I)

[0035] Wherein, R1 is selected from an alkyl group having 1 to 20 carbon atoms, an alkyl substituent, a phenyl group or a phenyl substituent; R2 and R3 are independently selected from a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkyl substituent, a phenyl group or a phenyl substituent.

[0036] In some preferred embodiments, the mass ratio of the nano smoke suppressant to the soybean aglycone-based benzoxazine resin is 0.1-10:90-100.

[0037] In some preferred embodiments, the preparation method specifically comprises: mixing the nano smoke suppressant with the soybean aglycone-based benzoxazine resin by at least one of a melting method, a physical blending method, and a solvent-assisted mixing method.

[0038] In some preferred embodiments, the process conditions used for the curing treatment include: curing at 160-170°C for 1-5h, curing at 170-180°C for 1-5h, curing at 180-200°C for 1-5h, curing at 200-220°C for 1-5h, and curing at 220-240°C for 1-5h.

[0039] In some more specific embodiments, the method for preparing the flame retardant and smoke suppressant benzoxazine nanocomposite material comprises the following steps: firstly, the dried nano smoke suppressant is evenly mixed with any one or more of the soybean aglycone-based benzoxazine resins in a certain proportion, then placed in a silicone mold, and prepared through a step curing process to obtain the flame retardant and smoke suppressant benzoxazine nanocomposite material.

[0040] Preferably, the ratio of the nano smoke suppressant to the soybean aglycone-based benzoxazine resin matrix is ​​0.1-10 parts: 90-100 parts.

[0041] Preferably, the mixing method includes any one of a melting method, a physical blending method, and a solvent-assisted mixing method.

[0042] Preferably, the curing procedure is 160-180°C / 1-5 hours, 180-200°C / 1-5 hours, 200-220°C / 1-5 hours.

[0043] The present invention adopts copper-loaded laser-induced graphene as a nano smoke suppressant and soybean aglycone-based benzoxazine with intrinsic flame retardancy and high carbonization property as a resin matrix. The combination of the two can significantly improve the flame retardancy of the nano-composite material and effectively suppress smoke release during combustion without the need for the use of halogen-containing or phosphorus-containing materials or a complicated modification process of the nano smoke suppressant.

[0044] Another aspect of the embodiments of the present invention further provides a flame retardant and smoke suppressing benzoxazine nanocomposite material prepared by the aforementioned preparation method.

[0045] Another aspect of the embodiments of the present invention further provides the use of the aforementioned flame retardant and smoke suppressant benzoxazine nanocomposite material as a high-performance resin matrix or structural material in the fields of electronic packaging, aerospace or rail transportation.

[0046] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0047] The copper-loaded laser-induced graphene nano-smoke suppressant and soybean aglycone-based benzoxazine used in the embodiments of the present invention are both homemade, and other raw materials are purchased from the market.

[0048] In the examples and comparative examples, the samples were tested according to the EN ISO 5659-2 toxicity test standard and using conventional testing instruments. 2 or 50KW / m 2 Under the condition of radiation heat source, the release of eight gases, including CO2, CO, HF, HCL, HCN, NO2, SO2, and HBr, was analyzed. The test time was 10 minutes, and the maximum smoke density and the content of various gases in the 4th minute were recorded.

[0049] In the embodiments and comparative examples, the combustion characteristics of the samples were tested according to the GB / T 2408 horizontal and vertical combustion test standard and using conventional testing instruments.

[0050] Example 1 (1) Preparation of benzoxazine / copper acetylacetonate composite solidified material: First, 15 g of phenol-4,4'-diaminodiphenylmethane type benzoxazine (PH-ddm type benzoxazine) and 1.5 g of copper acetylacetonate were dissolved in chloroform to obtain a homogeneous mixed solution. Secondly, the silicone mold containing the mixed solution was placed in a 60°C vacuum oven and vacuumed for 2 hours. Finally, a step-by-step temperature curing was performed to obtain a sheet-like solidified material. Among them, the curing conditions were 180°C for 2 hours and 205°C for 2 hours.

[0051] (2) Preparation of copper-loaded laser-induced graphene nano-smoke suppressant: The above-mentioned solidified material is subjected to laser ablation with specific parameters, and the surface ablation layer is peeled off and collected to obtain copper-loaded laser-induced graphene nano-smoke suppressant. The laser power during the laser processing is 20W. The scanning mode during the laser direct writing process is grating mode, the speed is 200mm / s, the pixel density is 1000 (PPI), the defocus distance is 1mm, and the z-axis value is determined according to the actual thickness of the substrate. The X-ray diffraction spectrum of phenol-4,4'-diaminodiphenylmethane type benzoxazine and nano-smoke suppressant is as follows Figure 1 shown.

[0052] The structure of daidzein-based benzoxazine is shown below:

[0053] (3) Preparation of flame-retardant and smoke-inhibiting benzoxazine nanocomposite materials: First, add 100 g of soybean aglycone-based benzoxazine and 1 g of nano smoke suppressant into a high-speed mixer and mix at high speed for 5 minutes. Secondly, add the mixed materials into a curing mold for step curing to obtain a flame-retardant and smoke-inhibiting soybean aglycone-based benzoxazine composite material. The curing conditions are: 160°C for 2 hours, 170°C for 2 hours, 180°C for 2 hours, 200°C for 2 hours, and 220°C for 2 hours.

[0054] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0055] Embodiment 2: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0056] (2) Preparation of copper-loaded laser-induced graphene nano-smoke suppressant: Same as Example 1.

[0057] The structure of daidzein-based benzoxazine is shown below:

[0058] (3) Preparation of flame retardant and smoke suppressant benzoxazine nanocomposite material: First, add 100g of soybean aglycone-based benzoxazine and 1g of nano smoke suppressant into a high-speed mixer and mix at high speed for 5 minutes; secondly, add the mixed materials into a curing mold for step curing to obtain a flame retardant and smoke suppressant soybean aglycone-based benzoxazine composite material. The curing conditions are: 160℃ for 1 hour, 170℃ for 1 hour, 180℃ for 1 hour, 200℃ for 1 hour, and 220℃ for 1 hour.

[0059] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0060] Embodiment 3: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0061] (2) Preparation of copper-loaded laser-induced graphene nano-smoke suppressant: Same as Example 1.

[0062] The structure of daidzein-based benzoxazine is shown below:

[0063] (3) Preparation of flame retardant and smoke suppressant benzoxazine nanocomposite material: First, add 100g of soybean aglycone-based benzoxazine and 10g of functionalized nano smoke suppressant into a high-speed mixer and mix at high speed for 5 minutes; secondly, add the mixed materials into a curing mold for step curing to obtain a flame retardant and smoke suppressant soybean aglycone-based benzoxazine composite material. The curing conditions are: 160℃ for 2 hours, 170℃ for 2 hours, 180℃ for 2 hours, 200℃ for 2 hours, and 220℃ for 2 hours.

[0064] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0065] Embodiment 4: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0066] (2) Preparation of copper-loaded laser-induced graphene nano-smoke suppressant: Same as Example 1.

[0067] The structure of daidzein-based benzoxazine is shown below:

[0068] (3) Preparation of flame retardant and smoke suppressant benzoxazine nanocomposite material: First, add 100g of soybean aglycone-based benzoxazine and 0.1g of functionalized nano smoke suppressant into a high-speed mixer and mix at high speed for 5 minutes; secondly, add the mixed materials into a curing mold for step curing to obtain a flame retardant and smoke suppressant soybean aglycone-based benzoxazine composite material. The curing conditions are: 160℃ for 2 hours, 170℃ for 2 hours, 180℃ for 2 hours, 200℃ for 2 hours, and 220℃ for 2 hours.

[0069] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0070] Embodiment 5: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0071] (2) Preparation of nano smoke suppressants loaded with copper laser-induced graphene: The laser-induced graphene method was used to transform the benzoxazine substrate containing copper acetylacetonate using a laser to obtain a functionalized nano smoke suppressant, wherein a carbon dioxide laser was used, and the laser power during the laser processing was 5W. The scanning mode during the laser direct writing process was a raster mode, the speed was 400mm / s, the pixel density was 500 (PPI), the defocus distance was 5mm, and the z-axis value was determined according to the actual thickness of the substrate.

[0072] The structure of daidzein-based benzoxazine is shown below:

[0073] (3) Preparation of flame retardant and smoke suppressing benzoxazine nanocomposite materials: Same as Example 1 Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0074] Embodiment 6: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0075] (2) Preparation of nano smoke suppressants loaded with copper laser-induced graphene: The laser-induced graphene method was used to transform the benzoxazine substrate containing copper acetylacetonate using a laser to obtain a functionalized nano smoke suppressant, wherein a carbon dioxide laser was used, and the laser power during the laser processing was 5W. The scanning mode during the laser direct writing process was a raster mode, the speed was 400mm / s, the pixel density was 500 (PPI), the defocus distance was 5mm, and the z-axis value was determined according to the actual thickness of the substrate.

[0076] The structure of daidzein-based benzoxazine is shown below:

[0077] (3) Preparation of flame retardant and smoke suppressing benzoxazine nanocomposite materials: Same as Example 1 Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0078] Embodiment 7: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0079] (2) Preparation of nano smoke suppressant loaded with copper laser-induced graphene: Same as Example 1 The structure of daidzein-based benzoxazine is shown below:

[0080] (3) Preparation of flame retardant and smoke suppressing benzoxazine nanocomposite materials: Same as Example 1 Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0081] Embodiment 8: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0082] (2) Preparation of nano smoke suppressant loaded with copper laser-induced graphene: Same as Example 1 The structure of daidzein-based benzoxazine is shown below:

[0083] (3) Preparation of flame retardant and smoke suppressing benzoxazine nanocomposite materials: Same as Example 1 Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0084] Embodiment 9: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0085] (2) Preparation of nano smoke suppressant loaded with copper laser-induced graphene: Same as Example 1 The structure of daidzein-based benzoxazine is shown below:

[0086] (3) Preparation of flame retardant and smoke suppressing benzoxazine nanocomposite materials: Same as Example 1 Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0087] Embodiment 10: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0088] (2) Preparation of nano smoke suppressant loaded with copper laser-induced graphene: Same as Example 1 The structure of daidzein-based benzoxazine is shown below:

[0089] (3) Preparation of flame retardant and smoke suppressing benzoxazine nanocomposite materials: Same as Example 1 Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0090] Embodiment 11: (1) Preparation of benzoxazine / copper acetylacetonate composite cured product: Same as Example 1.

[0091] (2) Preparation of nano smoke suppressant loaded with copper laser-induced graphene: Same as Example 1 The structure of daidzein-based benzoxazine is shown below:

[0092] (3) Preparation of flame retardant and smoke suppressing benzoxazine nanocomposite materials: Same as Example 1 Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0093] Comparative Example 1: The method is the same as that of Example 1, except that: there is no need to add the prepared nano smoke suppressant.

[0094] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0095] Comparative Example 2: The method is the same as that of Example 1, except that an equal amount of phenol-aniline benzoxazine is used instead of daidzein-based benzoxazine.

[0096] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0097] Comparative Example 3: The method is the same as that of Example 1, except that an equal amount of common graphene is used as the nano smoke suppressant to replace the nano smoke suppressant prepared in the present invention.

[0098] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0099] Comparative Example 4: The method is the same as in Example 1, except that copper acetylacetonate is absent.

[0100] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0101] Comparative Example 5: The method is the same as that of Example 1, except that an equal amount of copper acetylacetonate is used as the nano smoke suppressant to replace the nano smoke suppressant prepared in Example 1.

[0102] Sampling and analysis: Standard samples were made and the test performance is shown in Table 1 and Table 2.

[0103] Table 1 Gas component concentration in the fourth minute (PPM)

[0104] Table 2 Properties of the benzoxazine cured products obtained in Examples 1-11 and Comparative Examples 1-5 ; Note: t1 and t2 are the follow-up burning time of the first ignition and the follow-up burning time of the second ignition respectively.

[0105] It can be seen from the test data of 16 polybenzoxazine materials prepared by Examples 1 to 11 and Comparative Examples 1 to 5 that with the addition of functionalized nano smoke suppressants, the intrinsic flame retardancy of the polybenzoxazine materials is significantly improved, and the release rate of harmful gases during combustion is significantly reduced.

[0106] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0107] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a nano smoke suppressant, characterized in that: include: A copper source, phenol-4,4'-diaminodiphenylmethane type benzoxazine and a solvent are mixed, and then the solvent is removed, solidified and laser ablated to obtain a nano smoke suppressant of laser-induced graphene loaded with copper.

2. The preparation method according to claim 1, characterized in that: Specifically include: The copper source, phenol-4,4'-diaminodiphenylmethane type benzoxazine and a solvent are mixed, stirred and ultrasonically treated to prepare a homogeneous mixed solution; The homogeneous mixed solution is subjected to vacuum removal of solvent and stepwise temperature curing treatment to obtain a solidified product; Furthermore, the solidified material is subjected to laser ablation treatment and mechanical stripping treatment to obtain a nano smoke suppressant of laser-induced graphene loaded with copper.

3. The preparation method according to claim 2, characterized in that: The copper source includes any one or more combinations of copper acetylacetone compounds, dicyclopentadienyl compounds, carbonyl compounds, and organic phosphine compounds; And / or, the solvent includes any one or more combinations of acetone, tetrahydrofuran, chloroform, dichloromethane, N,N-dimethylformamide, and dimethyl sulfoxide; And / or, the mass ratio of the copper source to phenol-4,4'-diaminodiphenylmethane type benzoxazine is 1-20:80-99.

4. The preparation method according to claim 2, characterized in that: The temperature used for vacuum removal of solvent is 40-80°C; And / or, the process parameters of the step-temperature curing treatment include: curing at 160-180° C. for 1-10 hours, and then curing at 180-205° C. for 1-10 hours; And / or, the laser used in the laser ablation process includes a carbon dioxide laser; And / or, the laser power used in the laser ablation process is 5-25W; And / or, the scanning mode in the laser direct writing process used in the laser ablation treatment is a raster mode, the speed is 1-500 mm / s, the pixel density is 200-1200 PPI, and the defocus distance is 0-6 mm.

5. The nano smoke suppressant prepared by the preparation method according to any one of claims 1 to 4.

6. A method for preparing a flame retardant and smoke suppressing benzoxazine nanocomposite material, characterized in that: include: The nano smoke suppressant according to claim 5 is mixed with soybean aglycone-based benzoxazine resin and subjected to curing treatment to prepare a flame-retardant and smoke-suppressant benzoxazine nanocomposite material.

7. The preparation method according to claim 6, characterized in that: The daidzein-based benzoxazine resin has a structure as shown in formula (I): ; Formula (I) Wherein, R1 is selected from an alkyl group having 1 to 20 carbon atoms, an alkyl substituent, a phenyl group or a phenyl substituent; R2 and R3 are independently selected from a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkyl substituent, a phenyl group or a phenyl substituent.

8. The preparation method according to claim 6, characterized in that: The mass ratio of the nano smoke suppressant to the soybean aglycone-based benzoxazine resin is 0.1-10:90-100; And / or, the preparation method specifically comprises: mixing the nano smoke suppressant with soybean aglycone-based benzoxazine resin by at least one of a melting method, a physical blending method, and a solvent-assisted mixing method; And / or, the process conditions adopted for the curing treatment include: curing at 160-170°C for 1-5h, curing at 170-180°C for 1-5h, curing at 180-200°C for 1-5h, curing at 200-220°C for 1-5h, and curing at 220-240°C for 1-5h.

9. The flame retardant and smoke suppressing benzoxazine nanocomposite material prepared by the preparation method according to any one of claims 6 to 8.

10. Use of the flame-retardant and smoke-suppressing benzoxazine nanocomposite material according to claim 9 as a high-performance resin matrix or structural material in the fields of electronic packaging, aerospace or rail transportation.